Promotion of transnational textile hyper-consumption: fashion and excess as leitmotif - Luque González, Arturo (2017)
This paper’s main purpose is to analyze the enabling elements of the textile area that favor and promote unlimited hyper-consumption. To this end, the growth of the sector has been analyzed along with irradiating elements influenced by transnational firms that gravitate towards it, conditioning and boosting consumption. This new paradigm has inevitably led to a new concept of Good Living, society, consumption and fashion generating unequal effects, being the object of discussion, review and analysis.